2013
DOI: 10.2965/jwet.2013.153
|View full text |Cite
|
Sign up to set email alerts
|

Metal (Zn, Cu, Cd and Ni) Complexation by Dissolved Organic Matter (DOM) in Wastewater Treatment Plant Effluent

Abstract: Eight effluent samples were collected from four conventional activated sludge wastewater treatment plants (WWTPs) to determine the complexation of Zn, Cu, Cd and Ni by dissolved organic matter (DOM) in WWTP effluent. The collected effluents were subjected to determine the labile Zn, Cu, Cd and Ni concentrations using Empore TM chelating disk cartridge. It was observed that more than 55% of the dissolved metals were strongly complexed by ligands in the effluents. In addition, the Zn, Cu and Cd titration data ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…The data presented here shows that the complexation characteristics of the effluent-derived organic matter offer a substantially greater (DOC normalised) capacity to complex copper and zinc than those derived from natural sources, which was also consistent with findings from other similar studies (van Veen et al 2002; Sarathy and Allen 2005; Chaminda 2013). In their study, Sarathy and Allen (2005) proposed that up to 90% of the difference between river water and effluent copper complexation might be attributable to the influence of sulphide for which unprotonated sulphide clusters have been observed by others to form highly stable copper complexes (Rozan et al 2000) (thermodynamic stability constant log β >54); however, since the average binding affinity values for the effluents in the present study were lower than the values for the SRFA sample, the additional complexation capacity observed for the sewage effluents is unlikely to have been substantially attributable to such a strongly binding ligand.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The data presented here shows that the complexation characteristics of the effluent-derived organic matter offer a substantially greater (DOC normalised) capacity to complex copper and zinc than those derived from natural sources, which was also consistent with findings from other similar studies (van Veen et al 2002; Sarathy and Allen 2005; Chaminda 2013). In their study, Sarathy and Allen (2005) proposed that up to 90% of the difference between river water and effluent copper complexation might be attributable to the influence of sulphide for which unprotonated sulphide clusters have been observed by others to form highly stable copper complexes (Rozan et al 2000) (thermodynamic stability constant log β >54); however, since the average binding affinity values for the effluents in the present study were lower than the values for the SRFA sample, the additional complexation capacity observed for the sewage effluents is unlikely to have been substantially attributable to such a strongly binding ligand.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that wastewater effluent ligands are capable of binding trace elements present in the matrix to a greater degree than naturally derived DOC from, for example, standard Suwannee River humic and fulvic acids (Chaminda et al 2008, 2013) or that derived from road runoff (Chaminda et al 2010). Furthermore, effluent-derived DOC has been shown to be different in form compared to DOC derived from natural sources.…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of free ionic plus unstable complexed metals in these samples, which was measured by chelating disk cartridge, was 57 − 76% for Cu, 31 − 53% for Zn, 28 − 51% for Pb, 19 − 25% for Ni. The similar trend is reported in effluent samples of wastewater treatment plants (WWTPs) [46]. More than 55% of the dissolved metals were strongly complexed by ligands in the effluents.…”
Section: The Comparison Between Tuc and Hq (supporting
confidence: 82%
“…Therefore, the WWTP-derived metal-binding ligands with low SUVA 254 may also occur in the SRB main stream to some extent and potentially increase [Cu] Table S5). In addition to the anthropogenic ligands, hydrophilic DOM fraction and dissolved sulfides originated from urban effluents may affect trace 20 metal speciation due to their high binding affinities to trace metals (Chaminda et al, 2013;Louis et al, 2014;Matar et al, 2015;Rozan et al, 2000).…”
Section: Effects Of Effluent-derived Componentsmentioning
confidence: 99%